Urban Sanitation Problems and the Efforts to Overcome it in Medan City, 1909-1930s - Affandi, Kiki Maulana; Agustono, Budi; Zuska, Fikarwin (History Department, Semarang State University and Historian Society of Indonesia, 2022)
The growth of the city of Medan since the end of the 19th century had not only shown changes in terms of city infrastructure but also caused problems of urban sanitation such as slum settlements, industrial and household waste as well as river pollution. This study aims to explain sanitation problems in Medan City and the efforts to overcome them. This study used historical methods consisting of heuristics, source criticism, interpretation, and historiography. The sources used are archives, documents, city reports, city sheets, meeting minutes, contemporary newspapers, and other sources relevant to this study. The results show that the city's sanitation problems are caused by the habits of residents, plantation companies and institutions in the city government itself. These various sanitation problems were solved by developing urban sanitation despite having a limited city budget. This city sanitation development effort was focused on the aspects of public bathroom projects for the natives and the construction of a sewer system.Pertumbuhan Kota Medan sejak akhir abad 19 memperlihatkan perubahan dari sisi prasarana kota namun juga memberikan permasalahan sanitasi kota seperti permukiman kumuh, limbah industri dan rumah tangga serta pencemaran sungai. Studi ini bertujuan untuk menjelaskan permasalahan sanitasi di Kota Medan dan upaya penanggulangan yang dilakukan. Penelitian ini menggunakan metode sejarah yang terdiri dari heuristik, kritik sumber, interpretasi, dan historiografi. Sumber-sumber yang digunakan adalah arsip, dokumen, laporan kota, lembaran kota, notulen rapat, surat kabar sezaman, dan sumber lain yang relevan dengan studi ini. Hasil penelitian diperoleh bahwa masalah sanitasi kota disebabkan oleh kebiasaan penduduk, perusahaan perkebunan dan institusi pada pemerintah kota itu sendiri. Berbagai permasalahan sanitasi tersebut diatasi dengan membangun sanitasi kota meskipun memiliki anggaran kota yang terbatas. Usaha pembangunan sanitasi kota ini memperlihatkan konsentrasi dan kepedulian dalam bidang proyek kamar mandi umum bagi penduduk bumiputra dan pembangunan sistem saluran pembuangan limbah kota.Cite this article: Affandi, K.M., Agustono, B., Zuska, F. (2022). Urban Sanitation Problems and the Efforts to Overcome It in Medan City, 1909–1930s. Paramita: Historical Studies Journal, 32(1), 45-56. http://dx.doi.org/10.15294/paramita.v32i1.31353